The Existence of the Mosque as the Center of Islamic Civilization for the Community: A Case Study of The Baiturrahman Mosque in Ngawi - Hermawati, Kiki; Sabililhaq, Irhas; Nabila, Nisa Afrinauly (Fakultas Adab dan Ilmu Budaya UIN Sunan Kalijaga Yogyakarta, 2024)
Abstract: This research analyzes the role of the Baiturrahman Mosque in Ngronggi, Ngawi, as the center of Muslim civilization. The study employs qualitative methods using a case study approach. Data collection techniques include interviews and documentation. Data analysis is conducted using the Miles and Huberman method. The results of the study reveal that the Baiturrahman Mosque serves as a starting point for the development of community civilization. This is evident in initiatives such as the establishment of schools and Religious Affairs Offices around the mosque, as well as efforts to foster young people by involving them as officers and committee members in PHBI (Islamic holiday celebration) events. In addition to these programs, the Baiturrahman Mosque also runs a da'wah institution called majelis taklim. This majelis taklim not only provides guidance, education, and direction but also represents a new hope for enhancing the community's intelligence and enlightenment, particularly in religious and social aspects.Abstrak: Penelitian ini menganalisis peran Masjid Baiturrahman di Ngronggi, Ngawi, sebagai pusat peradaban umat Muslim. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus. Teknik pengumpulan data meliputi wawancara dan dokumentasi. Analisis data dilakukan menggunakan metode Miles dan Huberman. Hasil penelitian menunjukkan bahwa Masjid Baiturrahman berfungsi sebagai titik awal pengembangan peradaban masyarakat. Hal ini terlihat dari inisiatif seperti pendirian sekolah dan Kantor Urusan Agama di sekitar masjid, serta upaya membina generasi muda dengan melibatkan mereka sebagai petugas dan anggota panitia dalam acara PHBI (Perayaan Hari Besar Islam). Selain program-program tersebut, Masjid Baiturrahman juga mengelola lembaga dakwah yang disebut majelis taklim. Majelis taklim ini tidak hanya memberikan bimbingan, pendidikan, dan arahan, tetapi juga menjadi harapan baru untuk meningkatkan kecerdasan dan pencerahan masyarakat, terutama dalam aspek keagamaan dan sosial.